If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+4=-6x-9+4x
We move all terms to the left:
5x+4-(-6x-9+4x)=0
We add all the numbers together, and all the variables
5x-(-2x-9)+4=0
We get rid of parentheses
5x+2x+9+4=0
We add all the numbers together, and all the variables
7x+13=0
We move all terms containing x to the left, all other terms to the right
7x=-13
x=-13/7
x=-1+6/7
| 2(x+5)-4=4x-2(-5+x) | | (3x-1)+4x=-8 | | 700=13.5x+425 | | .75n=n+23 | | 2/7x+2=3/8x | | 8(3x-1)=26x+7-2x | | x/3-3x+2/6-1=4x/2 | | y-31/6=124/5 | | 12/x+8=5 | | 4(x-1)/6=4(x+2)/12 | | 15+5(x-4)=55 | | 4+10x=-3+3x^2 | | 20+4x=7x+5 | | 2x+5+3=6x+16 | | 13+2p=(-10) | | 0.003x+0.01=0.0005x-0.008 | | 10b+7=12 | | 12.50-0.40x=14.75-0.25x | | 5=8w-3w | | 58=402n | | 2x^2+5x+11=23 | | V+7v=48 | | 12=7v-v | | 3x=12x150 | | 2x-3.50=5x-3.25 | | X+4=2z | | 5=n/15 | | 4x-6/2×-3=7/×+1 | | 2x+((3x−1)/2)−((5x−2)/3)=2 | | t/9(3t+8)=t+8/18 | | 2x+3x−1 2−5x−2 3=2 | | 1/9(3t-8)=t+8/18 |